2014
DOI: 10.1136/vr.101669
|View full text |Cite
|
Sign up to set email alerts
|

Elevations in serum muscle enzyme activities in racehorses due to unaccustomed exercise and training

Abstract: Hereditary muscular disease is well described in racehorses, yet little is known about traumatic muscle disease associated with unaccustomed exercise or training. The objective of the study was to compare sedentary horses, racehorses undergoing training for the first time (unaccustomed exercise), and experienced racehorses during a training season (accustomed exercise) to investigate the effect of exercise and training on serum muscle enzyme activities and other variables. Horses were sampled prior to exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Previous studies suggest that mild elevations in GGT are a normal response to training, but the mechanism and relationship with athletic performance are unclear [1]. The repeated depletion and repletion of hepatic glycogen stores during intensive training and/or hepatocellular injury, as is seen in people engaged in ultra-long-distance running, have been proposed as possible causes [1,12]. Although increased serum GGT activity is almost exclusively associated with liver disease, GGT is expressed in several other tissues, and without determining tissue expression levels we cannot definitively rule out the possibility its increased activity was due to cellular damage outside the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that mild elevations in GGT are a normal response to training, but the mechanism and relationship with athletic performance are unclear [1]. The repeated depletion and repletion of hepatic glycogen stores during intensive training and/or hepatocellular injury, as is seen in people engaged in ultra-long-distance running, have been proposed as possible causes [1,12]. Although increased serum GGT activity is almost exclusively associated with liver disease, GGT is expressed in several other tissues, and without determining tissue expression levels we cannot definitively rule out the possibility its increased activity was due to cellular damage outside the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Of the markers evaluated, GGT is of interest because its activity is positively correlated with cumulative days in training, and has been associated with poor performance in horses with GGT activity greater than two times the upper limit of the reference range (i.e. ≥100 IU/L) [1][2][3]. GGT is an enzyme involved with glutathione metabolism that is found in almost all tissues; however, increased serum activity is almost exclusively related to liver disease, specifically cholestasis and hepatocellular necrosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…17 A study of racing Standardbred trotters found that acute strenuous exercise did not cause significant increases in SAA concentration 81 and there was only a weak correlation between SAA concentration and cumulative training days in training thoroughbreds followed for several months of training. 82 Overall, SAA concentrations seem to increase to a greater degree with endurance exercise as compared with shortdistance (including strenuous) work, with variations between types of exercise likely being subtle enough to make clinical utility of these findings minimal.…”
Section: Exercise and Serum Amyloid Amentioning
confidence: 91%
“…Studies have demonstrated that GGT activity is correlated to cumulative training load and racing frequency and considered a maladaptation to training. [37][38][39][40] Oxidative stress has been hypothesized as a cause. 28 The incidence of this increased GGT activity in racehorses in 1 study was 18%, 41 but in some stables it may be higher.…”
Section: Liver Enzyme Activity In Horses With Secondary Liver Diseasementioning
confidence: 99%